CPC-112 Predictors of Potentially Inappropriate Prescribing in Elderly Fallers. (12th March 2013) - O'Sullivan, D; Carroll, J; Meegan, C
Abstract : Background: A study to explore the rate of potentially inappropriate prescribing (PIP) in elderly fallers, and the impact of pharmacist-led medicines reviews was undertaken. Data relating to possible predictors of PIP, identified in the literature, were also collected. Purpose: To investigate the following factors as predictors of PIP in elderly fallers: Demographic data Drugs classes Polypharmacy Materials and Methods: The following data were collected as part of a larger study: Demographic data: age, gender and days since admission at time of fall Number of regular medicines Name and class of PIMs identified Results: Sixty patients were included in this study, 34 (56.7%) of whom were male. The median age was 79 years (range: 29). Patients were taking a median of 9 regular drugs (range: 17). Twenty-one (35%) patients were prescribed ≥1 PIM at the time of their fall. Gender was not a predictor of PIP, with 13 male and 8 female patients prescribed ≥1 PIM (P = 0.548). Excessive polypharmacy (≥10 medications) was identified as a positive predictor of PIP. Participants prescribed ≥1 PIM were taking a mean of 10.86 regular medicines; those not prescribed ≥1 PIM were taking a mean of 7.67 regular medicines (p < 0.001). A drug from each class in section H of the STOPP criteria was identified at least once. Benzodiazepines were the most frequently prescribed PIM drug class, accounting for 59% of PIMs overall. Six patients in the baseline group and 7 in the intervention study were prescribed a benzodiazepine. The most commonly prescribed PIM was temazepam. Conclusions: Polypharmacy is a predictor of PIP. Patients prescribed ≥1 PIM were taking on average 3 more regular medicines than those who were not prescribed ≥1 PIM (p < 0.001). Gender was not a predictor of PIP. No conflict of interest.